A FEMINIZAÇÃO DA MIGRAÇÃO NO CONTEXTO DA PROTEÇÃO DO DIREITO À SAÚDE - Najah Jamal Daakour Barakat (2021)
The aim of the present research was to discuss about the phenomenon of female migration in the context of protecting the international right to the migrant women’s health. The justification for the proposal is related to the very recurrent problem of migration, since the migratory flows, at the present time, are permeated by several factors, collated in human rights violations, where the presence of women in the migratory context has a complex nuance, mainly referring to health, with elements such as pregnancy, pregnant, routine exams that prevent the women's health, among other problems and which are also intrinsically linked to the imperative need to protect women's health rights, inserted in the context of migratory flows. The research issue is based on the following question: Does the right to health of migrant woman have protection in the international context of human rights? The deductive approach method was used in this bibliographical research. The argument is based on texts by authors such as: Arendt (2007); Balera and Silveira (2013); Castles (2010); Comparato (2013); Gregori (2013); Jubilut and Apolinário (2010); Lessa (2016); Lundgren-Alves (2018); Peres and Baeninger (2016); Piovesan (2012); Sassen (2016). Economic and social development, based on a New International Economic Order, is of fundamental importance to achieving full health for all and to reducing the gap in health status that exists between developed and developing countries. The promotion and protection of the population's health are essential to maintain economic and social development and contribute to a better quality of life and peace in the world. This theme has been exhaustively analyzed, however, there are still gaps to be filled given the complexity and richness of the subject, considering that the migratory process has increased in all places and countries, forming a latent exodus of the poorest, in search of their livelihood and that of your family. Keywords: Migration. Women. International Migration. Right to Health. Feminization.